Computational approaches for screening for bacterial inhibitors from the plant Malabar nut (Journal of Pharmaceutical Negative Results, 2022)
Bacterial infections are a growing world-wide problem. Bacterial infections are now known to assassinate annually more people than malaria. One of the best practices of the ancient time for the treatment of bacterial infection was Ayurvedic. On analyzing the latest survey about the plant possessing the antibacterial activity, it was identified that the plants Malabar nut possess various pharmacological properties. The native of the plant was India and was commonly called as Adusa which belongs to the family of Acanthaceae. In the current research work, totally 102 phytochemical compounds were retrieved from the plant Malabar nut through literature survey. Using PubChem databases, the two dimensional structure were identified only for 84 compounds. Virtual screening was carried out for these compounds and the result predicted that only 28 compounds were screened to be active drug molecules. The bacterial protein Cytochrome P450 14-alpha-sterol demethylases (CYP51) was responsible for most of the bacterial disease caused to human. Using PDB databases, the three dimensional structure of the protein were retrieved which were further used for docking process. Out of 28 compounds only 1 compound predicted the best binding interaction with the protein using docking software.